المَوضُوعيَّة في دراسة الأديان: إشكالية المفهوم والمصطلح: OBJECTIVITY IN RELIGIOUS STUDY: PROBLEM OF CONCEPT AND TERMINOLOGY - Mubarak Bawadi, Abdullah Ahmed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
The article touched on the problematic concept of objectivity and its possibility to be applied as in the Holy Qur’an, social and human sciences. It also focuses on the fundamental issues, principles and solutions to the objectivity problems contained in the religious studies in the Qur’an, as well as discussing the issues of Sharī`ah law. The research showed that the Sharī`ah opinion derived from the Holy Qur’an in all these cases which invalidate the Western concept of the fact of objectivity. It also criticized the method of relying on the contemporary terms in taking decisions of Sharī`ah cases. It also analysed the opinion of the discrepancy between the objectivity, the ideological and tradition judgments, the religious criticism, self-abstraction and the religious belief, the relativity of truth and the religious knowledge. The research aimed to emphasize the importance of the commitment to use the Sharī`ah terminologies in making scientific decisions including the term of objectivity and distinguishing the scientific mistakes related to this term. In treating this topic, this article used the inductive method, delving into the scientific articles in the Islamic thoughts. Furthermore, it used the critical method to discuss some issues related to the problem statement of the research. The results confirm the truth of objectivity and its concept in religious studies, the possibility of applying it according to a system of principles, fundamentals and Sharī`ah Law legitimation.